IMPLEMENTATION OF THE FREE NUTRITIOUS FOOD PROGRAM AND THE QUALITY OF EDUCATION: AN EDUCATIONAL MANAGEMENT PERSPECTIVE IN INDONESIA - Monalisa (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The Free Nutritious Meals (MBG) program is a strategic policy intervention designed to improve students' nutritional status, thereby supporting the quality of education in Indonesia. However, empirical evidence suggests that the impact of school meal programs on educational outcomes is not always direct or uniform, because these outcomes are influenced by various mediating and moderating factors. This article aims to synthesize scientific evidence on the implementation of the MBG and its implications for educational quality from an educational management perspective. This study uses a systematic qualitative review approach to empirical publications published between 2004 and 2025. Of the 266 documents identified through database searches and citation chains, the 50 most relevant articles were analyzed in depth using thematic analysis. The synthesis results indicate that MBG contributes to improvements in students' nutritional and health status, thereby enhancing prerequisites for learning, such as attendance, concentration, motivation, and class participation. The causal pathway from improved nutritional status to academic achievement is non-linear and is mediated by other factors, including the quality of teaching, the learning environment, and students' socio-economic conditions. The findings confirm that variations in MBG's impact across regions are primarily explained by differences in the quality of managerial implementation, cross-sectoral coordination capacity, sensitivity to the socio-cultural context, and the level of stakeholder engagement. This article proposes a conceptual model of MBG implementation in which implementation management directly influences both nutritional status and learning readiness, which act as mediators, while regional context and stakeholder engagement serve as moderators for these relationships. These findings contribute to the education policy literature by clarifying the mechanisms through which school feeding programs operate as educational management policies and as investments in human resource development.